Waste to Wealth: A Study on Effectiveness of Tech-Enabled Business Models for Sustainability (Bmfs) Of Solid Waste Management Enterprises in India - Chandra Sekhara Srinivas Nanduri (Journal of Informatics Education and Research, 2025)
Indian Startups and Enterprises play a pivotal role in addressing the sustainability challenges specially in ‘Waste Management’ sector. Literature provides theoretical to little understanding on their business models, technologies role, effectiveness and stakeholders’ perspective from Indian context. Existing business models are either excessively focussed on producing economic value or profits and not enough value for environment and society or their focus is more on dry waste processing. Startups don’t have enough resources for business model experimentation and established Enterprises constrained/confined by their pre-existing business models, organization cultures and routines. Moreover, the entrepreneurs are ahead in practice exploring and exploiting business models compared to academic knowledge about them. Therefore, improving our understanding of the Business Models for Sustainability (BMfS) and the effectiveness of tech-enabled business models would thus contribute to academic; practice and managers becomes focus of this research. Towards that, a detailed literature review to identify research gaps and opportunities are identified and presented in this research article.